Interfacing inorganic halide perovskites with metal-organic frameworks: Color tunable emission, energy transfer, and advanced anti-counterfeiting application - Kachhap S.; Rai A.K.; Singh A.K.; Singh S.K. (My University, 2025)
This work presents an inorganic halide perovskite (CsPbBr3) is interfaced with a europium metal-organic framework (Eu-MOF). The presence of characteristic absorption edge and band edge emission of CsPbBr3 reveal a successful formation of CsPbBr3@Eu-MOF hybrid. The bi-flower morphology of Eu-MOF has tetragonal structure with space group P4322. The conical part of the bi-flower consists of many squared rods of edge length 200 nm. The CsPbBr3@Eu-MOF shows color-tunable emission under different excitation wavelengths whose CIE color coordinate covers the entire green to red region. The maximum luminous efficacy of the optical radiation achieved is 359 lm/W, and the maximum color purity is 94.4 %, which is significant for optical applications. Further for anti-counterfeiting application, a pattern “LMDD” is encrypted on four different substrates and the color change is captured under different excitation wavelengths. The results show that CsPbBr3@Eu-MOF is highly suitable for encryption and decryption of security codes particularly on plastic surface. © 2024 Elsevier Ltd